2020
DOI: 10.2217/fca-2020-0126
|View full text |Cite
|
Sign up to set email alerts
|

Cardiology and COVID-19: do We have Sufficient information?

Abstract: Novel coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2, which originated in Wuhan (China), transformed into a worldwide pandemic. The short span associated with the spread of the virus and its varied manifestations presents a steep learning curve for many clinicians on the front-line of treatment. Cardiology is one such affected area. This paper details the signs and symptoms of cardiovascular disease resulting from COVID-19, including its proposed pathophysiology, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…[43][44][45][46] Additionally, multiple reports have suggested that patients with underlying cardiovascular comorbidities such as heart failure are at higher risk of severe disease and mortality due to COVID-19. 44,[47][48][49][50] Collectively, the rescreening of patients with worsening cardiovascular disease was indeed necessary. For patients attending the Department of Internal Medicine, the higher rescreening rate in the Division of Infectious Diseases may be because approximately half of the quarantined patients belonged to that division, while the lower rescreening rate in the Division of Hematology and Oncology could possibly be explained by the fact that around three-quarters of the cases were repeatedly included due to recurrent fever caused by the underlying disease or anticancer therapy.…”
mentioning
confidence: 99%
“…[43][44][45][46] Additionally, multiple reports have suggested that patients with underlying cardiovascular comorbidities such as heart failure are at higher risk of severe disease and mortality due to COVID-19. 44,[47][48][49][50] Collectively, the rescreening of patients with worsening cardiovascular disease was indeed necessary. For patients attending the Department of Internal Medicine, the higher rescreening rate in the Division of Infectious Diseases may be because approximately half of the quarantined patients belonged to that division, while the lower rescreening rate in the Division of Hematology and Oncology could possibly be explained by the fact that around three-quarters of the cases were repeatedly included due to recurrent fever caused by the underlying disease or anticancer therapy.…”
mentioning
confidence: 99%
“…Once the virus attaches, this leads to myocardial infarction. Angiotensin-converting enzyme-2 dependent myocardial infarction leads to the decreased angiotensin-converting enzyme-2 expression [ 16 ]. The infection causes macrophage infiltration in the heart leading to myocarditis [ 17 ].…”
Section: Pathophysiologymentioning
confidence: 99%
“…Signs of myocardial injury can be seen with elevated cardiac troponin markers, abnormal ECG findings and magnetic resonance-based imaging (Fig. 1 ) [ 16 , 20 ].…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…The lockdown has increased the social anxiety in people as they were totally away from each other during those days when people with social anxiety disorder come into public places, they start feeling they have lost their comfortable zone and thus try to avoid going into public places 10 . The symptoms of social anxiety disorder manifest physically and psychologically ranging from symptoms of social anxiety including nausea, excessive sweating, tachycardia, shivering, etc 11 .…”
Section: Introductionmentioning
confidence: 99%